System-technological method of management of modernization of technical objects - Сидорчук, Олександр Васильович; Демидюк, Микола Анатолійович; Поліщук, Лариса Миколаївна; Сятковський, Олександр Анатолійович; Демчук, Іван Вікторович (Eastern-European Journal of Enterprise Technologies, 2012)
In the article the method of system-technological modernization of technical objects, providing a system analysis of their processes